Pre-pregnancy counseling for women with heart disease: A prospective study. (1st August 2017) - Cauldwell, M.; Steer, P.J.; Swan, L.; Patel, R.R.; Gatzoulis, M.A.; Uebing, A.; Johnson, M.R.
Abstract: Background: Women with cardiac disease and their infants are at a greater risk of mortality and morbidity during pregnancy. Expert groups recommend preconception counseling (PCC) for all women with cardiac disease so they are made aware of these risks. We have run a specialist maternal cardiac clinic since 1996. The aim of this study was to evaluate the experience of women who have received PCC within an established multidisciplinary tertiary clinic and to establish their views regarding the counseling they received. Methods: Single centre prospective study using a patient questionnaire was given to women attending a specialist cardiac preconception counseling clinic from November 2015 to August 2016, with analysis of descriptive data and free text comments from the questionnaire responders. Results: 40/65 returned patient questionnaires. Prior to the consultation fewer than half felt well informed regarding how their heart disease could impact upon pregnancy but a similar proportion felt nonetheless that they would be able to have a healthy pregnancy. Women reported two main areas of concerns, their own health (whether they would survive a pregnancy) and the health of their child. 15% of women reported that these concerns had prevented them from pursuing a pregnancy. Women reported high satisfaction rates with the clinic. Conclusions: There is an increasing demand for PCC services for women with cardiac disease; our study is the first attempt to determine both the acceptability and the impact of PCC from the patient perspective. Patients reported a high level of satisfaction with the service provided.